Effect of Anesthetics on Red Blood Cell Membranes - P. Yu. Alekseyeva; V. V. Moroz; V. Yu. Vasilyev; G. R. Kaziyev; Ye. K. Kozlova; A. M. Chernysh; M. S. Bogushevich; A. P. Kozlov; U. A. Bliznyuk (Общая реаниматология)
Objective: to comparatively analyze the effect of anesthetics on red blood cell membranes in whole blood and its suspension.Materials and methods. The blood sampled from healthy donors was studied. A total of 260 tests using whole blood and its suspension were carried out. The study has considered the effect of esmerone, listenone, and hexanal on red blood cell membranes and revealed a specific response to each of them.Results. Esmerone given at a concentration of 1 µl and 10 µl of the drug per ml of blood in the suspension impaired the structure of membranes, without showing it worth in the whole blood. Hexenal at a concentration of 2 µl and 20 µl of the drug per ml of blood strengthened the membrane and increased the voltage failure threshold, but this result was more pronounced in the suspension and in the whole blood. The effect of listenone at a concentration of less than 2 µl was slightly noticeable, but the drug strengthened the membrane and induced a pronounced membranous structural derangement when given at a concentration of 20 µl of the drug per ml of blood or higher in the whole blood and in the suspension, respectively.Conclusion. Knowledge about the effects of the agents on blood cells may assist anesthesiologists to prevent possible complications during and after surgical interventions.